Energy and exergy assessments of a perlite expansion furnace in a plaster plant - Gurturk, Mert; Öztop, Hakan Fehmi; Hepbasli, Arif (Pergamon-Elsevier Science Ltd, 2013)
In this study, energy and exergy assessments of a perlite expansion furnace in a plaster factory are performed. Chemical properties of the perlite and its application areas are described. Energy and exergy relations according to the First and Second Law of Thermodynamics are derived. Energy and exergy efficiencies, losses and exergy destructions are calculated based on the measurements obtained from the system. Evaluations of environmental impact, energy management and economic are finally generalized according to the obtained results. Energy and exergy efficiencies of the furnace are determined to be 66% and 26%, respectively. Reference temperature effects on exergy efficiency, destruction and sustainability index are also presented. The results showed that the furnace has not been well designed in terms of thermal aspects due to high energy and exergy losses and the manufacturer producing the perlite expanded should establish an energy management structure. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Exergy; Energy audit; Perlite; Perlite expansion furnace; Furnace